PRAKTIKALITAS E-MODUL FLIPPED BOOK BERBASIS EMPLOYABILITY SKILL LEARNING UNTUK KOMPETENSI SPA THERAPIES SISWA SMK KECANTIKAN - Astuti, Murni; Rahmiati, Rahmiati; Dewi, Siska Miga; Thaitami, Siti Hajar; Koto, Rahmat Desman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Learning at SMK Beauty faces various challenges, such as the need for learning media relevant to industry needs, inappropriate learning strategies, and low student motivation. To overcome this challenge, this study develops and tests the practicality of the e-module flipped book based on employability skill learning. This media is designed to improve students' technical competence and work skills as spa therapies relevant to the industrial world. The research uses the ADDIE development method and involves validators and ten small class students at SMKN 6 Padang as practical test subjects. The study results show that the e-module has a high level of practicality. Validators gave an average rating of 86.25% in the convenience category, while students gave an average rating of 87% in the convenience category. This e-module is considered easy to use, efficient in learning time, and visually appealing. In addition, integrating employability skills in flip-book-based learning encourages the development of students' communication, teamwork, and time management skills. Thus, this e-module has the potential to be an innovative solution to improve the competence of Spa Therapies students of Beauty Vocational School.Keywords: Flipped Book, Employability Skill Learning, Spa Therapies, Practicality, Beauty Vocational School